Maintenance of Bilge Pump on Ship Trawl SPL IX Owned PT. Sinar Pesona Laut - Saridu, Muhammad Al Mu’Min; Ziliwu, Boby Wisely (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
A pump is a machine or device that raises liquid from a low surface to a higher surface or moves liquid from a low-pressure to a high-pressure area. A centrifugal pump is a machine or equipment used to provide energy to a fluid (liquid) based on the centrifugal force generated by a rotating impeller. So that the liquid can be moved or moved from one place to another. As it receives energy through the impeller, the fluid velocity will increase. This kinetic energy is then converted into compressive energy by the pump housing (casing) in the form of a spiral (volute) or a centrifugal pump or fixed blades (diffuser) surrounding the impeller so that the liquid exits the pump at a high speed. The maintenance method for the bilge pump auxiliary machine is carried out in 6 stages, namely, the first stage opening the filter box, the second stage removing the inner filter and filter box cover gasket, the third stage installing new anti-rust on the inside of the filter box cover, the fourth stage removing the box filter connecting faucet and the bilge pump pipeline, the fifth stage opens the connection of the pipe and the bilge pump, the sixth stage ensures that all components of the bilge pump are firmly installed and perform operational test